Volunteer Satisfaction at the Boundary of Public and Nonprofit: Organizational- and Individual-Level Determinants - Henderson, Alexander C.; Sowa, Jessica (Public performance & management review, 2019)
How human capital is managed continues to be a question of great importance in the study of public administration and is one that cuts across studies of public and nonprofit organizations and their operations. Fire departments in the United States, which often take the form of nonprofit organizations, are a unique setting to study questions of human capital management and related topics. This study contributes to the growing dialogue about essential public service volunteers by examining volunteering in what is often thought of as a traditional public service: the fire service. This article is guided by the following question: what individual and organizational factors contribute to the satisfaction of volunteer firefighters? The findings presented here indicate that volunteer firefighters are more likely to be satisfied when they are motivated by public service values, find support for these activities among their close social circles, and find that their voluntary work is characterized by both autonomy and feelings of efficaciousness.